the Measurement of Soil Carrying Capacity on Road Construction Plans as an Effort to Harmonize Mining Companies with the Kalirejo Community: Measurement of Soil Carrying Capacity on Road Construction Plans - firmansyah, firhad; Rizqi Prastowo (ReTII, 2022)
Mining is the activity of digging, loading, and transporting material from the mining front to the point of sale. Material transportation activities certainly require infrastructure like access to the point of sale. That access is the road. Roads in a rural area are designed according to their designation, where village roads can only accept vehicle loads < 8 tons (PP No. 43 of 1993). Based on the actual field, rural roads are also used as roads for mining activities, namely transporting mining materials, resulting in damaged roads. This study aims to determine the soil bearing capacity (DDT) on a 1.3 km long road with 13 direct measurement points in the field using DCP (Dynamic Cone Penetration). The smallest DDT value is 5.6 kg/cm2, and the largest is 10.2 kg/cm2, so the value of the carrying capacity of the soil compared to the load of the conveyance indicates a mismach. It is necessary to conduct a DDT study for road pavement plans to create harmonization with the hope that the road can be safely used for mining activities and village community activities in a relatively long period.